Analisis Strategi Pemasaran Dengan Menggunakan Metode Marketing Mix Dalam Menghadapi Persaingan - Raja Sakti Putra Harahap; Safaruddin Munthe; Sa'diah Khairani Lubis (-, 2022)
The research aims for a marketing strategy using the marketing mix method in dealing with competition at the Cafe District Nineteen Binjai. This study uses a qualitative approach. Sources of data used are primary and secondary data. Data collection techniques with interviews and documentation. The data analysis technique used SWOT analysis. The results of this study indicate that, the marketing mix strategy of Cafe District Nineteen Binjai through a product strategy by guaranteeing and maximizing product quality and providing the best service, the marketing mix strategy of Cafe District Nineteen Binjai through a pricing strategy. Prices are set by considering direct factors in the form of raw material costs and production costs. The Cafe District Nineteen Binjai marketing mix strategy is through the chosen place strategy, namely choosing the area around the school, and the market (Pekan 18). The place was chosen because it is close to the settlement as well as close to the center of the crowd. And also with the Grabfood application media. The marketing mix strategy for the Cafe District Nineteen Binjai is through promotional strategies, namely sales promotion, word of mouth marketing and interactive marketing through Instagram and the Grabfood application to make it easier for modern consumers to transact.